Christ for us sermons - Martin, Hugh, 1822-1885 (Edinburgh, Scotland Banner of Truth, 1998)
Includes bibliographical references.
Keywords: Martin, Hugh, -- 1822-1885; Jesus Christ -- person and offices -- lectures, essays, lectures